Avaliação da toxicidade aguda e subaguda e efeitos metabólicos de Astrocaryum huaimi Mart. em ratos diabéticos - Santos, Mirelly Marques Romeiro (2022)
The aim of the present study was to evaluate the toxicological potential and the metabolic effects of tucumã (Astrocaryum huaimi Mart.) peel and pulp in diabetic rats. The tucumã fruits were collected at Fazenda São Sebastião, in the municipality of Limeira do Oeste, Minas Gerais, Brazil. Physical, physico-chemical, mineral content, quantification of fatty acids and analysis of antioxidant compounds were performed. For the acute and subacute oral toxicity test, 60 Swiss mice were used, divided into: acute toxicity and subacute toxicity. Possible behavioral, hematological, biochemical and histopathological changes were evaluated. For the experiment to standardize the induction of type 2 diabetes through the association of cafeteria diet and streptozotocin (STZ), 40 male Wistar rats were used, divided into a control group and diabetic groups: 30, 35 and 40 mg/kg of STZ. The following parameters were evaluated: anthropometric, water and feed intake, biochemical and histopathological. For the evaluation of the metabolic effects of tucumã flour (FT) 43 male Wistar rats were used, divided into 2 control groups: one group received commercial food, a diabetic control group + cafeteria diet and three diabetic groups + cafeteria diet + FT in 3 different doses: 2%, 4% and 8% TF. Induction of diabetes was performed with a single injection of STZ at a dose of 35 mg/kg. The groups were evaluated through anthropometric and biochemical analyses, insulin resistance test and histological parameters. The tucumã fruits presented in their composition appreciable levels of lipids (18.28 g.100g-1), fiber (35.95 g.100g-1), vitamin C (14.35 mg.100g-1), iron ( 5.15 mg.100g-1), potassium (1,776.05 mg.100g-1) and unsaturated fatty acids (58.86%). The analysis of the bioactive compounds revealed that the acetone extract, followed by the ethanol extract, presented the highest antioxidant capacity and the highest level of phenolic compounds and tannins. In the acute and subacute toxicity test, the supplementation of tucumã peel and pulp meal demonstrated absence of lethality, organ damage and changes in the general behavior of mice, indicating that all doses can be considered safe for these animals, providing preliminary data. on the toxic profile of Astrocaryum huaimi Mart. The experiment developed for standardization of induction of type 2 diabetes proved to be an efficient and low-cost model, with no loss of animals during the experiment. Streptozotocin doses of 35 and 40mg/kg were effective in mimicking the metabolic characteristics of the disease in humans, confirmed by the presence of polydipsia, hyperglycemia, altered biochemical tests, insulin resistance and liver, pancreas and kidney damage. In the experiment that evaluated the metabolic effects of FT, the animals that received the highest dose of FT supplementation had higher values of water consumption, blood glucose and triglycerides, as well as lower insulin and C-peptide values, when compared to the control group. FT supplementation was not efficient in reversing or minimizing the metabolic effects caused by type 2 diabetes.